Transformasi Perilaku Penonton di Era Digital: Faktor-Faktor yang Mempengaruhi Kunjungan ke Bioskop di Indonesia - Salsabila, Nayla; Annisa, Sarah; Fadhila, Syifa; Khairani, Syifa Nur (Universitas Al Azhar Indonesia, 2025)
The rapid growth of digital streaming platforms has significantly altered consumer behavior in the entertainment industry, posing challenges for traditional cinemas. This study examines the factors influencing Indonesian moviegoers' intention to visit cinemas by replicating Patil et al. (2023)’s model based on stakeholder theory. Through a quantitative approach, data were collected from Indonesian respondents who had visited cinemas within the past six months. The study analyzes key variables, including theater preference, ticketing preference, movie branding, and movie genre, along with moderating factors such as control belief, social companion, and promotional strategies. The findings confirm that theater preference significantly influences the intention to watch movies in cinemas, while ticketing preference does not have a notable impact. Additionally, commercial promotions were found to weaken the influence of movie branding on audience intent. These results highlight the need for Indonesian cinemas to emphasize immersive viewing experiences and strategic marketing efforts to remain competitive in the digital era.